2023
DOI: 10.1126/science.adh1506
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Rydberg moiré excitons

Abstract: Rydberg excitons, the solid-state counterparts of Rydberg atoms, have sparked considerable interest with regard to the harnessing of their quantum application potentials, but realizing their spatial confinement and manipulation poses a major challenge. Lately, the rise of two-dimensional moiré superlattices with highly tunable periodic potentials provides a possible pathway. Here, we experimentally demonstrate this capability through the spectroscopic evidence of Rydberg moiré excitons (X RM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…In ref. [40], Hu et al found a Rydberg moiré exciton, which is the counterpart of the solid Rydberg atom. Rydberg moiré excitons have similar properties to Rydberg atoms and are more compatible with modern semiconductor technology.…”
Section: Discussionmentioning
confidence: 99%
“…In ref. [40], Hu et al found a Rydberg moiré exciton, which is the counterpart of the solid Rydberg atom. Rydberg moiré excitons have similar properties to Rydberg atoms and are more compatible with modern semiconductor technology.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no observed dependence of the band-edge energies on the stacking alignment r t . The recent observation of Rydberg moiré excitons in WSe 2 utilized a similar approach to modulate the properties of the top layer TMD by adjusting the moiré period generated from a twisted graphene bilayer. This provides a new control parameter for tailoring the minibands and is distinct from the typical moiré superlattices .…”
Section: Moiré Pattern From 2d Materialsmentioning
confidence: 99%
“…Very recently, emergence of exotic phenomena like isospinpolarized metals, orbital multiferroicity, integer and even fractional quantum anomalous Hall effects have been reported for multilayered rhombohedral graphene or its moiré structures. 4 These states can potentially be used for developing ultralow-power electronics for information storage, transportation, and fault-tolerant topological quantum computation.…”
Section: Editorialmentioning
confidence: 99%